Anemia in Hidradenitis Suppurativa, Hepcidin as a Diagnostic Tool. (11th September 2019) - Ghias, Mondana; Cameron, Sophie; Shaw, Fiona; Soliman, Yssra; Kutner, Allison; Chaitowitz, Mark; Cohen, Steven; Gil, Morayma Reyes
Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease characterized by recurrent nodules, abscesses, and dermal tracts. We recently reported a high prevalence of anemia in HS patients. These data led to the hypothesis that chronic inflammation in HS predominantly causes anemia of chronic disease (ACD) through upregulation of IL-6 and hepcidin, a key regulator of iron homeostasis. Hepcidin is widely accepted as a marker distinguishing ACD from iron deficiency anemia (IDA) in inflammatory conditions. The purpose of this study was to measure serum hepcidin in HS patients to classify the type of anemia observed in this cohort. We measured hematologic data, inflammatory markers, and serum hepcidin using an enzyme-linked immunosorbent assay (ELISA; R&D Systems) in 55 patients with varying degrees of HS severity. Independent Student t tests and one-way ANOVA were used to compare hepcidin levels in HS patients with anemic and nonanemic states. Of 55 HS patients evaluated in this study, 42 (76%) were female and the average age was 37.6 ± 13.2 years. The mean hemoglobin (Hb) was 12.2 ± 2.0 g/dL and mean hepcidin was 19.5 ± 12.9 ng/mL. Anemic patients (n = 26) with reduced iron stores (ferritin ≤30 ng/mL) had significantly lower hepcidin than anemic patients with adequate iron stores (9.7 ± 15.8 ng/mL vs 23.8 ± 11.1, P = .03). Elevated hepcidin in this subset suggests that ACD is the predominant cause of anemia. Analysis by ANOVA also found that hepcidin levels were significantly greater in patients with more severe HS, as measured by HS-Physician Global Assessment scores ( P = .005). Hepcidin may serve as a surrogate biomarker for active disease and inflammation in HS. These findings affirm the utility of hepcidin as a promising tool for distinguishing IDA from ACD and, in turn, help identify HS patients in whom dietary iron supplementation is unlikely to be beneficial.